MAGNESIUM IN THE TREATMENT AND PREVENTION OF MIGRAINE - E. S. Akarachkova; A. R. Artemenko (Сеченовский вестник, 2012)
Magnesium — intracellular cation — is important in many pathological processes including the pathogenesis of migraine. Magnesium deficiency in patients with migraine may be developed as a result of genetic inability to absorb magnesium and its excessive loss with stress because of low nutritional intake and a number of other reasons. Migraine magnesium deficiency contributes in changing the activity of NMDA-receptors, distribution of cortical depression hyperaggregation platelets, affects the function of serotonin receptors and metabolism of many neurotransmitters. Intravenous magnesium-containing drugs show high efficacy in the treatment and prevention of migraine.